Induction of caspase dependent apoptosis by α-Mangostin in breast cancer cells - Navya Atluri,; Vasavi Thirumalanadhuni,; Uma Maheswari devi Palempalli, (International Journal of Phytomedicine, 2014)
Apoptotic potential of α-Mangostin (98-99.99% HPLC purified)was evaluated in vitro using MDA-MB-231 human breast cancer cell line as a model system. The nucleosomal DNA gel electrophoresis was performed to delineate the mechanism of α-Mangostin treated MDA-MB-231 cells death. The dose-dependent oligonucleosomal fragmentation of DNA was observed in α-Mangostin treated cells. Flow cytometrywas performed to confirm the apoptotic potential of α-Mangostin (10µM) on MDA-MB-231 cells. The control cells showed only 1.85% of hypodiploid DNA and the percentage increased to 13.70% on exposure of cells to α-Mangostin. Caspase-3, a critical regulator of cell death, was detected in α-Mangostin treated MDA-MB-231 cells by Immunocytochemical analysis. These results demonstrated the expression of caspase-3 in MDA-MB-231 cells exposed to 10µM of α-Mangostin. The results suggest that α-Mangostin induced cell death was by the activation of cell death pathway particularly mediated by caspase-3.